Spatial exploration patterns determine navigation efficiency: Trade-off between memory demands and distance travelled - MAKANY, Tamas (Institutional Knowledge at Singapore Management University, 2007)
A total of 41 participants explored a novel square-shaped environment containing five identical boxes each hiding a visually distinct object. After an initial free exploration the participants were required to locate the objects first in a predetermined and subsequently in an optional order task. Two distinct exploration strategies emerged: Participants explored either along the main axes of the room (axial), or in a more spatially spread, circular pattern around the edges of the room (circular). These initial exploration strategies influenced the optimality of spatial navigation performance in the subsequent optional order task. The results reflect a trade-off between memory demands and distance efficiency. The more sequential axial strategy resulted in fewer demands on spatial memory but required more distance to be travelled. The circular strategy was more demanding on memory but required less subsequent travelling distance. The findings are discussed in terms of spatial knowledge acquisition and optimality of strategy representations.